Tailored second harmonic generation inTi-diffused PPLN waveguides usingmicro-heaters - Babai-Hemati, Jonas; vom Bruch, Felix; Herrmann, Harald; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Cryogenic electro-optic modulation in titanium in-diffused lithium niobate waveguides - Thiele, Frederik; vom Bruch, Felix; Brockmeier, Julian; Protte, Maximilian; Hummel, Thomas; Ricken, Raimund; Quiring, Viktor; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Journal of Physics: Photonics)
Abstract Lithium niobate is a promising platform for integrated quantum optics. In this platform, we aim to efficiently manipulate and detect quantum states by combining superconducting single photon detectors and modulators. The cryogenic operation of a superconducting single photon detector dictates the optimisation of the electro-optic modulators under the same operating conditions. To that end, we characterise a phase modulator, directional coupler, and polarisation converter at both ambient and cryogenic temperatures. The operation voltage <?CDATA $V_{π/2}$?> V π / 2 of these modulators increases, due to the decrease in the electro-optic effect, by 74% for the phase modulator, 84% for the directional coupler and 35% for the polarisation converter below 8.5 <?CDATA $\,K$?> K . The phase modulator preserves its broadband nature and modulates light in the characterised wavelength range. The unbiased bar state of the directional coupler changed by a wavelength shift of 85 <?CDATA $\,nm$?> n m while cooling the device down to 5 <?CDATA $\,K$?> K . The polarisation converter uses periodic poling to phasematch the two orthogonal polarisations. The phasematched wavelength of the utilised poling changes by 112 <?CDATA $\,nm$?> n m when cooling to 5 <?CDATA $\,K$?> K .
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Materials Screening for Disorder‐Controlled Chalcogenide Crystals for Phase‐Change Memory Applications - Xu, Yazhi; Wang, Xudong; Zhang, Wei; Schäfer, Lisa; Reindl, Johannes; vom Bruch, Felix; Zhou, Yuxing; Evang, Valentin; Wang, Jiang‐Jing; Deringer, Volker L.; Ma, En; Wuttig, Matthias; et al. (Advanced Materials)

Waveguide resonator with an integrated phase modulator for second harmonic generation - Stefszky, Michael; Santandrea, Matteo; vom Bruch, Felix; Krapick, S.; Eigner, Christof; Ricken, R.; Quiring, V.; Herrmann, Harald; Silberhorn, Christine (Optics Express)

Cryogenic electro-optic polarisation conversion in titanium in-diffused lithium niobate waveguides - Thiele, Frederik; vom Bruch, Felix; Quiring, Victor; Ricken, Raimund; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optics Express)